СOMPLICATIONS OF ENDODONTIC TREATMENT: PECULIARITIES OF CLINICAL SIGNS, DIAGNOSIS - O.V. Hurzhii; S.V. Kolomiiets (Український стоматологічний альманах, 2018)
Endodontic lesions take leading positions in the structure of modern dentistry. General areas of the displacement of filling material or instruments because of the poor quality of endodontic treatment have been established, and the features of clinicoroentgenological and neurological manifestations of the complications of endodontic dentistry have also been determined.